The Role of Immune Checkpoint Blockade in the Hepatocellular Carcinoma: A Review of Clinical Trials - Ozer, Muhammet; George, Andrew; Goksu, Suleyman Yasin; George, Thomas J.; Sahin, Ilyas (Frontiers in Oncology, 2021)
The prevalence of primary liver cancer is rapidly rising all around the world. Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. Unfortunately, the traditional treatment methods to cure HCC showed poor efficacy in patients who are not candidates for liver transplantation. Until recently, tyrosine kinase inhibitors (TKIs) were the front-line treatment for unresectable liver cancer. However, rapidly emerging new data has drastically changed the landscape of HCC treatment. The combination treatment of atezolizumab plus bevacizumab (immunotherapy plus anti-VEGF) was shown to provide superior outcomes and has become the new standard first-line treatment for unresectable or metastatic HCC. Currently, ongoing clinical trials with immune checkpoint blockade (ICB) have focused on assessing the benefit of antibodies against programmed cell death 1 (PD-1), programmed cell death-ligand 1 (PD-L1), and cytotoxic T-lymphocyte- associated antigen 4 (CTLA-4) as monotherapies or combination therapies in patients with HCC. In this review, we briefly discuss the mechanisms underlying various novel immune checkpoint blockade therapies and combination modalities along with recent/ongoing clinical trials which may generate innovative new treatment approaches with potential new FDA approvals for HCC treatment in the near future.